PENGETAHUAN WANITA USIA SUBUR TENTANG DETEKSI DINI KANKER SERVIKS PUSKESMAS KAMPUNG PERSATUAN KOTA TANJUNGBALAI TAHUN 2018 - ERLINA ESTHER ROTUA SIRINGORINGO (LP2MTBM MAKARIOZ, 2020)
The study aims to determine the knowledge of women of childbearing age about early detection of cervical cancer. This method of research uses descriptive design. The research was conducted in Puskesmas Kampung Persatuan Tanjungbalai City to 32 women of childbearing age. The measuring instrument used is a questionnaire with 20 questions with good results, enough and less developed by researchers. The results showed that from 32 respondents obtained women of childbearing age with good knowledge as much as 3 people (9.4%), with enough knowledge as much as 14 people (43.7%) and knowledgeable as much as 15 people (46.9%). Based on the results of the research is made known to the community especially women of childbearing age to increase knowledge and conduct health screening of cervical cancer, and to the government to provide better health information directly or indirectly about cervical cancer to reduce the incidence rate of cervical cancer.